Using Mind-Mapping in Improving Students’ Writing Skills of Eleventh Grade at MAS Yaspen Nurul Huda Serapuh - Yusrah; Yuli Pera Fitria (Journal of Applied Linguistics, 2024)
This study investigated the use of mind mapping as a strategy for improving the writing skills of eleventh-grade students at MAS YasPen Nurul Huda Serapu. This study focused on 24 students who struggled to organize their ideas and effectively communicate them in written English. To measure the impact of mind mapping on students' writing abilities, the study used a combination of observation, instructor interviews, and several exams across three cycles. The first data in Cycle I revealed that students had a low average GPA of 57.66, indicating a substantial need for intervention. Students' average scores rose gradually as they used mind mapping, reaching 65.50 in Cycle II and 80.50 in Cycle III, surpassing the KKM standard of 72. The findings demonstrated that mind mapping effectively helps students organize their thoughts and improve their writing skills. This research highlights the potential of innovative teaching methods like mind mapping in enhancing educational outcomes and suggests further integration of such techniques in the curriculum to support student learning. Keywords: Mind mapping; Writing skills